Efficacy of galcanezumab in patients with episodic cluster headaches and a history of preventive treatment failure. (27th May 2021) - Plato, Brian; Andrews, J Scott; Rettiganti, Mallikarjuna; Tockhorn-Heidenreich, Antje; Bardos, Jennifer; Wenzel, Richard; Kuruppu, Dulanji; Ambrosini, Anna
Objective: The efficacy of galcanezumab was evaluated in patients with episodic cluster headache and history of preventive treatment failure. Methods: In the randomized, 8-week, double-blind study (CGAL), patients with episodic cluster headache received once-monthly subcutaneous injections of galcanezumab 300 mg or placebo. Patients who completed CGAL and enrolled in an open-label study were queried for preventive treatment history. In a subset of patients with a known history of failure of verapamil or any other prior preventive treatment, a post hoc analysis of least square mean change from baseline in weekly cluster headache attack frequency across Weeks 1 to 3 was assessed. Results: Fifteen patients provided data for known history of prior preventive treatment failure (6 placebo, 9 galcanezumab), of whom 11 failed verapamil. The mean reduction in the weekly frequency of cluster headache attacks was greater with galcanezumab compared to placebo among patients with prior preventive treatment failure (8.2 versus 2.4); mean difference 5.8 (95% confidence interval [CI] 2.0, 13.6) and among patients with verapamil failure (10.1 versus 1.6); mean difference 8.5 (95% CI 0.4, 16.7). Conclusion: In this exploratory analysis of patients with a known history of prior preventive treatment failures, treatment with galcanezumab resulted in greater mean reductions in weekly cluster headache attacks compared with placebo. ClinicalTrials.gov: NCT02397473 (I5Q-MC-CGAL) NCT02797951 (I5Q-MC-CGAR)